Features of the resource species Miscanthus sacchariflorus (Maxim.) Hack. when introduced in West Siberia - Yu. A. Gismatulina; V. V. Budaeva; G. V. Sakovich; O. Yu. Vasilyeva; G. A. Zueva; A. S. Gusar; O. V. Dorogina (Вавиловский журнал генетики и селекции)
Here we provide a scientific justification and experimental support for the choice of easily renewable cellulosic feedstock Miscanthus sacchariflorus (Maxim.) Hack. in order to obtain high-quality nutrient broths therefrom for bacterial cellulose biosynthesis. The plant life-forms promising for breeding were screened under introduction conditions at the Central Siberian Botanical Garden, SB RAS, and this study was thus aimed at investigating the full and reduced ontogenetic patterns; cellulose and noncellulosic contents, including lignin; and duraminization of vegetative (feedstock source) organs throughout the seasonal development. The full ontogenetic patterns of the plants grown from seeds that had been collected in native habitats were compared to show that M. sacchariflorus and M. sinensis Anderss. accessions are distinguished by longer being at the most vulnerable developmental stages: seedlings and plantlets. Hence, it is preferable to cultivate seedlings on protected ground, and plantations are advisable to establish with more stable cloned vegetative material. The chemical compositions of the whole plant, leaf and stem separately, from seven M. sacchariflorus harvests were examined to reveal a rise in cellulose content and a drop in noncellulosic content with plantation age. The Miscanthus stem was found to contain more cellulose than the leaf, regardless of the plant age. The overall cellulose content was 48−53 %, providing a rationale for studies of bacterial cellulose biosynthesis in a M. sacchariflorusderived nutrient medium. Since high lignin content is undesirable for technological processes concerned with biosynthesis of bacterial cellulose, we performed histochemical assays of transverse sections of the culms to monitor the seasonal course of lignification. Our results suggest that the specific time limits for harvesting the aboveground biomass as a feedstock be validated by histochemical data on the seasonal course of lignification of M. sacchariflorus sprouts. To sum up, the examined chemical composition of M. sacchariflorus grown in the Siberian climate conditions demonstrated its prospects as a source of glucose substrate, the basic component of good-quality nutrient media for biosynthesis of bacterial cellulose.